Permacultura alimentar: uma semente rumo à restauração da cultura de vida - Campos Filho, Hermano José Maia (2022)
Since food is the primary source of vitality and energy that animates the functioning of natural systems, they assume a central role in the challenge of restoring the culture of life in the midst of the civilizing crisis announced by the ill-living that emerge as a cumulative and synergy of the risks and damages arising from modernity. Based on the principles and practices of Permaculture that guide ways of occupying and interacting with the world through care (including and integrating us) with nature and with other living beings, this work seeks to show the fundamental connections between the food cycle and permacultural design, in order to conceive the bases of a food Permaculture and its relations with the field of Ecogastronomy. The developments of such fundamentals and connections from the perspective of food culture are developed and presented in a systemic approach, centered on nature's cuisine and translate into health and well living practices. In order to highlight the link between the integrated cycles of food culture and permacultural places as a core value for the restoration of the culture of life, we analyzed the experience of Sítio Floresta (Eusébio, CE) as a restorative seed and, based on interviews, reports and mapping of connections with the surroundings, we described the regenerative potential of this network in the context of a commercial subdivision and the modes of use and occupation of space conventionally practiced.